2013
DOI: 10.1111/eea.12096
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness and competitiveness of irradiated light brown apple moths

Abstract: The sterile insect technique (SIT) potentially provides a socially acceptable approach for insect eradication of new pest incursions. The light brown apple moth, Epiphyas postvittana (Walker) (Lepidoptera: Tortricidae), was discovered in Berkeley (CA, USA) in 2006, leading to an incursion response that included this technology. In this study, we assessed factors affecting mating success from a bisex release of irradiated moths: effects of radiation dose on male multiple mating, male flight competition, female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…The relationship of radiation dose and mating frequency of the light brown apple moth was found to be significantly negative (Stringer et al 2013). In addition, the production of the sex pheromone by the females declined significantly with increasing doses of radiation.…”
Section: Mating Compatibility and Competitivenessmentioning
confidence: 96%
See 2 more Smart Citations
“…The relationship of radiation dose and mating frequency of the light brown apple moth was found to be significantly negative (Stringer et al 2013). In addition, the production of the sex pheromone by the females declined significantly with increasing doses of radiation.…”
Section: Mating Compatibility and Competitivenessmentioning
confidence: 96%
“…In head-to-head comparisons of flights of irradiated light brown apple moth males and non-irradiated males toward a pheromone lure in a wind tunnel, irradiated males reached the lure first only 31% of the time (Stringer et al 2013). Light brown apple moth males were irradiated as pupae at intervals up to a dose of 300 Gy, and their flight success was assessed in a wind tunnel equipped with flight track recording software.…”
Section: Flight Ability Of Sterile Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these programs faced issues of stockpiling insects, synchrony, losses during extended storage, and other tradeoffs. Placement of irradiated pupae to emerge in the field has been done experimentally, but requires adequate protection from predation (Stringer et al 2013). The Australian painted apple moth program in New Zealand was an operational example using pupal irradiation ) and this approach was also explored for gypsy moth (Reardon and Mastro 1993).…”
Section: Sterile With Competitive Field Performancementioning
confidence: 99%
“…Despite attempts to model the effects of bi-sex or male-only releases of moths that suggested little benefit from females (Kean et al 2011), there is evidence for a background contribution of the female moths through communication disruption of males from calling virgin females, despite their irradiationreduced attractiveness and pheromone titre (Stringer et al 2013;Suckling et al 2006). Further, it has been suggested that there may be a benefit from sterile females acting as a ''sperm sink'' for wild males thereby reducing wild male fertility, which could contribute to part of the observed effect of population suppression.…”
Section: Operational Strategiesmentioning
confidence: 99%